KONTRIBUSI LINGKUNGAN KELUARGA DAN CARA BELAJAR TERHADAP HASIL BELAJAR SISWA KELAS X - Adhitya Hidayat; Edidas Edidas (Universitas Negeri Padang, 2019)
This research is motivated by the problem of low learning outcomes in the Basic Electricity and Electronics subject at SMK Negeri 1 Sumbar. The purpose of the study was to reveal how much the contribution of the family environment and how to learn about learning outcomes. The research method used in this study is descriptive correlational. The study population 96 people and the sample 49 people. The research sample was determined using simple random sampling technique. The results of data analysis showed that (1) the family environment and the way of learning of students together contributed significantly to student learning outcomes by 37.99%. (2) family environment significantly contributes to student learning outcomes by 23.88%, (3) student learning methods contribute significantly to student learning outcomes by 26.39%. So it can be concluded that he better the family environment and effective and efficient ways of student learning, the higher the learning outcomes. Keywords: Student team achievent division, learning models, learning outcomes, experiment, control